Digital image correlation analysis of vertical strain for corrugated fiberboard box panel in compression. Issue 3 (22nd January 2019) - Kueh, Celia S. L.; Dahm, Karl; Emms, Grant; Wade, Kelly; Bronlund, John E.
Abstract : This work was aimed at examining the overall contributions to displacement of panels of compressed boxes, such as panel compression strain and flap and crease displacements. 3D digital image correlation (DIC) was used to analyse motion of side panels of corrugated fiberboard regular slotted containers. The vertical displacement and the vertical component of strain of the panel face during box compression test were examined. Measuring displacements of the whole compressed box with DIC enables measurement of the in‐plane compression of a panel in isolation from the horizontal fold or crease zone displacement, without having to test tube sections of the box to infer or extract the in‐plane panel compression behaviour. Detailed study of two box designs in three representative test cases was presented, which in future could be extended to other box designs. At peak load, the in‐plane compression of the panels, calculated from the average vertical component of the strain along the right edge of the long panel of the box, was 3% to 6% of total crosshead displacement for the test cases. At peak load, the portion of the box compression associated with bottom box flaps or crease zone crushing was 48% to 59% of total crosshead displacement for the different cases. The analysis showed that the majority of the vertical displacement of the box occurred in the top and bottom creased folds and that these folds are responsible for the low apparent in‐plane stiffness of a box. Abstract : 3D digital image correlation (DIC) was used to analyse the separate contributions of the in‐plane compression of panels and the horizontal fold displacements to the overall vertical displacement of whole compressed boxes, without having to test tube sections of the box. At peak load, the in‐plane compression of the panels and the bottom box flaps crushing was, respectively, 3% to 6% and 48% to 59% of the total crosshead displacement for three representative test cases.